Exploring the Just Noticeable Interaction Stiffness Differences of an Impedance-Controlled Series Elastic Actuator - Velasco Guillen, Rodrigo Jose; Schofer, Felix; Bliek, Adna; Beckerle, Philipp (Actuators, 2023)
The integration of a passive elastic element in series between a motor and its load is popular in many human–robot interaction scenarios. By virtually imposing elastic behavior on the motor, an impedance control can act as a second stiffness to such an actuator. In this study, we investigated how participants perceived the different stiffness settings in a series elastic actuator by measuring the Just Noticeable Difference (JND) of the real stiffness of the elastic element and the virtual stiffness introduced by impedance control. We conducted a user study during which participants interacted with an impedance-controlled Series Elastic Actuator through a lever. During the user study, we varied the real stiffness of the elastic element and the virtual stiffness. We found that participants seem to perceive both the virtual stiffness and the real stiffness in the same way and in accordance to Weber’s law, which states that the stiffness JND is always equal to a fraction of the initial stiffness. Following these findings, we concluded that the impedance controller can implement an effective virtual stiffness with a behavior comparable to a real torsional spring. Therefore, a system combining real and virtual stiffness can simulate a single combined stiffness for a user interacting with it.
Keywords: just noticeable difference; impedance control; elastic actuation; psychophysics